Equitable access to a personalized treatment with the OncoCREAN national strategy in pediatric patients with acute lymphoblastic leukemia from the Mexican Social Security Institute - Lopez Aguilar, Enrique; Del Campo Martinez, Angeles; Rioscovian Soto, Ana; Ayala-Contreras, Karen; Zapata-Tarrés, Marta; Cuéllar Mendoza, Miguel Enrique; Betanzos Cabrera, Yadira; Zevada-Mosti, Regina; Payán Romo, Sheyla; Esquer Cota, Oscar Omar; Zazueta Mérida, Pamela; Anaya Aguirre, Susana Elizabeth; et al. (Frontiers in Oncology, 2025)
IntroductionThe Mexican Social Security Institute (IMSS) was created in 1943 as the main public institution in Mexico.MethodsIn 2020, the OncoCREAN (Centros de Referencia Estatal para la Atención del Niño y de la Niña con Cáncer) strategy was established and consists of reference centers of Pediatric Oncology created to provide equitable access to pediatric patients with cancer in Mexico and toimprove the disease survival through standardized immunophenotyping, harmonized diagnosis, homogenized treatment, staff training, and complication response.ResultsAt 12 months of follow-up, overall survival is 89.9% in pediatric patients with acute lymphoblastic leukemia; we have no early death, and the main cause of death is still infection.DiscussionThe current procedure in terms of immune molecular diagnosis is to send samples to the first national system of samples reference for the immunological diagnosis of leukemias based on immunophenotyping in the Cytomics Laboratory of the IMSS Research Center in Puebla, as a strong collaborative alliance. We present a narrative description of the strategy as preliminary results.